Pengaruh Social Media Marketing dan Celebrity Endorser Terhadap Purchase Intention Minuman Merk Chatime Melalui Brand Awareness - Kevin Suparta; Eka Bertuah (Masyarakat Ekonomi Syariah Bogor, 2025)
The purpose of this study is to analyze the influence of social media marketing and celebrity endorsers on purchase intention, with brand awareness acting as a mediating variable. This study employs a purposive sampling method involving 170 respondents residing in the Greater Jakarta area (Jabodetabek) who have previously purchased and consumed Chatime beverages. The data were collected through an online survey using Google Forms and analyzed using PLS-SEM with the help of SmartPLS 4 software. The results of this study show that social media marketing has a positive effect on brand awareness. Furthermore, celebrity endorsers are also proven to have a positive influence on brand awareness. Brand awareness, in turn, significantly affects purchase intention. Social media marketing has a significant impact on purchase intention, while celebrity endorsers do not have a direct significant effect on purchase intention. However, social media marketing significantly affects purchase intention through brand awareness, and celebrity endorsers also have a significant indirect influence on purchase intention through brand awareness. This study is expected to serve as a basis for consideration and evaluation for the company in efforts to enhance brand awareness through various strategies, such as social media marketing and the use of celebrity endorsers, with the ultimate goal of increasing customers' purchase intention. The results of this study provide evidence of the implications of consumer behavior theory, indicating that purchasing decisions are influenced by several factors, including those related to the variables in this research namely media influence, product branding, and social groups..